SOSIALISASI DAN WORKSHOP PEMBUATAN PESTISIDA NABATI SERAI WANGI (PENAWANG) DI DESA KEMIRI SIDOARJO: SOSIALISASI DAN WORKSHOP PEMBUATAN PESTISIDA NABATI SERAI WANGI (PENAWANG) DI DESA KEMIRI SIDOARJO - Budi Prabowo; Eric Raynaldo Handy Saputra; Krisna Bayu Prasetiyo; Agnes Monalisa Putri Saluat (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The socialization activity on the use of citronella as a botanical pesticide in Kemiri Village, Sidoarjo, aims to minimize the use of chemical pesticides that can pollute the environment and pose health risks. Kemiri Village, with its potential in agriculture and home gardens, faces challenges from pests that damage crops. Although chemical pesticides are effective, they have long-term negative impacts such as soil and water contamination, and health risks. This socialization introduced the women of the PKK (Family Welfare Program) in RW 01 of Kemiri Village to botanical pesticides, particularly those made from citronella, which are more environmentally friendly and safer. The activities included delivering material on the importance of botanical pesticides and conducting a workshop on making